2015
DOI: 10.4025/reveducfis.v26i1.24693
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à hipertensão arterial em professores da educação básica

Abstract: RESUMOO objetivo do estudo foi analisar a pressão arterial elevada e os fatores associados a essa alteração pressórica em professores da educação básica. Foi realizado um estudo transversal em 200 professores de Viçosa-MG, com média de idade 43,2 + 10,2 anos. Foram avaliadas variáveis antropométricas, bioquímicas, pressóricas e número de passos diários. Calculou-se a análise de regressão linear múltipla para verificar a associação entre as variáveis. Foram encontrados 20% de hipertensos, com estes obtendo maio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
1
16

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 25 publications
(20 reference statements)
1
2
1
16
Order By: Relevance
“…Thus, it is suggested that such factors must be worked through practice of physical exercise and nutritional guidance, which contribute to prevention and a better control of SAH (31) . It is important to note that central obesity is involved in the metabolic syndrome genesis, and is responsible for emergence of resistance to insulin, SAH and dyslipidemia, therefore increasing cardiovascular risk of individuals (32) . The infection treatment can lead to appearance of some associated conditions, such as high levels of triglycerides, total cholesterol and LDL cholesterol increase, in addition to decrease in HDL cholesterol (33) .The association between dyslipidemia and SAH may also be a result of hypercholesterolemia contribution to raise arterial pressure through activation of the renin-angiotensin-aldosterone system, reduction of nitric oxide availability, endothelial dysfunction, among other factors involved (32) .However, we observed that diet of PLWHA, in general, is rich in fats and cholesterol and poor in fiber, combined with a low ingestion of vegetables, fruits and dairy products, which leads to dyslipidemia (11) .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is suggested that such factors must be worked through practice of physical exercise and nutritional guidance, which contribute to prevention and a better control of SAH (31) . It is important to note that central obesity is involved in the metabolic syndrome genesis, and is responsible for emergence of resistance to insulin, SAH and dyslipidemia, therefore increasing cardiovascular risk of individuals (32) . The infection treatment can lead to appearance of some associated conditions, such as high levels of triglycerides, total cholesterol and LDL cholesterol increase, in addition to decrease in HDL cholesterol (33) .The association between dyslipidemia and SAH may also be a result of hypercholesterolemia contribution to raise arterial pressure through activation of the renin-angiotensin-aldosterone system, reduction of nitric oxide availability, endothelial dysfunction, among other factors involved (32) .However, we observed that diet of PLWHA, in general, is rich in fats and cholesterol and poor in fiber, combined with a low ingestion of vegetables, fruits and dairy products, which leads to dyslipidemia (11) .…”
Section: Discussionmentioning
confidence: 99%
“…Santos;Gigante (2001), também mencionam baixa adesão à prática de exercícios físicos entre os diabéticos atendidos pelo programa ESF na Região Sul do Brasil. Sujeitos diagnosticados com DM tendem a apresentar maior percentual de gordura corporal e índice de massa corporal que seus congêneres sem diabetes (LIN et al, 2015), e esses parâmetros indicadores de sobrepeso/obesidade estão relacionados à menor capacidade cardiorrespiratória e nível de atividade física PEREIRA et al, 2014;MOREIRA et al, 2014;OLIVEIRA et al, 2015). Desta maneira, é possível que o baixo valor de prática de exercícios físicos referido não seja efeito da presença do DM, mas possa ser um fator Rev.…”
Section: Discussionunclassified
“…Por tanto, é necessário estabelecer o NAF dessa população, como forma de buscar uma melhora no controle e ação por parte dos profissionais envolvidos no tratamento dessas enfermidades. Dentre os procedimentos de mensuração dos níveis de atividade física é possível citar o acelerômetro (16) , análise de prontuários (17) e o International Physical Activity Questionnaire (IPAQ), sendo que o último é habitualmente empregado em estudos de base populacional (16,18) . Estabelecer qual a prevalência do sedentarismo nessa população poderá auxiliar na tomada de decisão sobre medidas para atenuar esse estado, além de colaborar para a construção de dados recentes para uma cidade do interior de Minas Gerais que apresenta características culturais e sociais próprias.…”
Section: Introductionunclassified